Electromigration in lead-free solder joints under high-frequency pulse current: An experimental study. (November 2013) - Yao, Wei; Basaran, Cemal
The insatiable demand for miniaturization of consumer electronics has brought continuing challenges in the electronic packaging field. As a consequence, immense information processing duties, high current density and large joule heating are exerted on the package, which makes electromigration and thermomigration a serious reliability issue. In this study, high frequency pulse current electromigration degradation experiments were carried out on Sn96.5%Ag3.0%Cu0.5 (SAC305 - by weight) solder joints. During the test, frequency, current density and duty factors are used as controlling parameters. The nominal current density varied from1 . 0 × 10 5 A cm 2 to2 . 1 × 10 5 A cm 2, pulsed direct current frequency ranged from 2 MHz to 10 MHz and duty factor varied between 30% and 80% with a controlled ambient temperature at 70℃. It was observed that mean time to failure was inversely proportional to the current density and duty factor. Higher frequency leads to a shorter lifetime within the frequency range we studied. Scanning electron microscope image shows that damage develops at both current crowding corners and the skin layer of solder joints. A mean time-to-failure relationship of lead-free solder joints under pulsed current loading is proposed based on the experimental data.